2023
DOI: 10.1371/journal.pone.0291270
|View full text |Cite
|
Sign up to set email alerts
|

Climate change as a driver of insect invasions: Dispersal patterns of a dragonfly species colonizing a new region

Diego Gil-Tapetado,
Diego López-Collar,
José F. Gómez
et al.

Abstract: The dragonfly Trithemis kirbyi Sélys, 1891 recently colonized Western Europe from North Africa. Since its first record in the Iberian Peninsula in 2007, the species has been spreading northward and has become naturally established in the central and eastern Iberian Peninsula, the Balearic Islands and southern France. Despite its worldwide distribution, its rapid colonization of the western Mediterranean area occurred only very recently. The aims of this study were to evaluate (1) whether the species’ colonizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…As temperature increases, higher latitudes and elevations are expected to warm, hence receiving more warm-tolerant species [15]. It is in keeping with this hypothesis that in Europe, many Odonata species have already expanded their distribution northward [5,7,9,13]. In South Korea, Shin et al [11] documented the northward expansion of Ischnura senegalensis between 1980 and 2020.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…As temperature increases, higher latitudes and elevations are expected to warm, hence receiving more warm-tolerant species [15]. It is in keeping with this hypothesis that in Europe, many Odonata species have already expanded their distribution northward [5,7,9,13]. In South Korea, Shin et al [11] documented the northward expansion of Ischnura senegalensis between 1980 and 2020.…”
Section: Introductionmentioning
confidence: 85%
“…Thus, T. annulata is advancing rather fast in Italy, particularly considering the 34 km/year observed over 7 years in northern Italy. However, for its congener Trithemis kirbyi Gil-Tapetado et al [13] reported that this species has a high dispersal potential and can disperse an average of 430 km per year and this ability to cross large distances quickly has been confirmed by sightings of this species on isolated islands in the Mediterranean basin [54]. When considering Odonata in general, the advance of the northern limit is slower.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations